Arnaud Buchs, Observer, caractériser et comprendre la pénurie en eau. Une approche institutionnaliste de l’évolution du mode d’usage de l’eau en Espagne et au Maroc - Arnaud Buchs (Revue de la Régulation)
Contrary to a-historical and technical analyses centred on physical water shortage, in this PhD dissertation we develop a social-contingent approach in which water use is fundamental. The empirical corpus is based on an analysis of the evolution of the “water use mode” in Almeria (Andalusia) and in Marrakech and Agadir (Morocco) between the end of the 19th century and today. We propose four chronological stylised facts that define four stages of the living cycle of a water use mode stamped as “hydraulicist”. On the other hand, we mobilize a syncretic institutionalist approach to characterize the mode and to understand the determinants of its crisis (described in the framework of a new typology of crises). Finally, we show how a new mode attempts to address the limitations of the previous one. Nevertheless, it actually does not imply a paradigm shift but corresponds to a “crisis regime”.